2019
DOI: 10.1371/journal.pone.0217245
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and molecular characterization of Chlamydia trachomatis in pregnant women from Córdoba, Argentina: A prospective study

Abstract: Background Chlamydia trachomatis causes the most prevalent bacterial Sexual Transmitted Infection. In pregnant women, untreated chlamydial infections are associated with abortions, premature rupture of membranes, postpartum endometritis, low birth weight and transmission to the newborn. In Có rdoba, Argentina, there is little knowledge about the prevalence of Chlamydia trachomatis in women in their third trimester of pregnancy, so, the aim of this study was to evaluate Chlamydia trachomatis prevalence and geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
2
4
2
5
Order By: Relevance
“…These results are in concordance with a study from India, which detected more prevalence of C.trachomatis in patients with abnormal cytology (31.5%) in comparison with normal cytology (5.8%) in women with complaints of vaginal discharge attending STI clinic in a tertiary care hospital in New Delhi [ 30 ]. On the other hand, other studies showed different results, such as local studies: Jordá, detected 8.5% C.trachomatis prevalence in symptomatic (vaginal discharge, pruritus, pelvis pain) and asymptomatic women with a request for a vaginal exudate study [ 31 ] and Kiguen, 6.9% in pregnant women, older than 14 years having 35 weeks of gestation [ 32 ], all results lower than our prevalence detected. Other studies, conducted by Ji, detected similar prevalence of C.trachomatis in women with normal and abnormal cytology, 7.1 and 7.2%, respectively, in China [ 5 ] and Costa Lira, detected to genital C.trachomatis in 9.02% in women who used public health services with abnormal cytology [ 25 ].…”
Section: Discussioncontrasting
confidence: 93%
“…These results are in concordance with a study from India, which detected more prevalence of C.trachomatis in patients with abnormal cytology (31.5%) in comparison with normal cytology (5.8%) in women with complaints of vaginal discharge attending STI clinic in a tertiary care hospital in New Delhi [ 30 ]. On the other hand, other studies showed different results, such as local studies: Jordá, detected 8.5% C.trachomatis prevalence in symptomatic (vaginal discharge, pruritus, pelvis pain) and asymptomatic women with a request for a vaginal exudate study [ 31 ] and Kiguen, 6.9% in pregnant women, older than 14 years having 35 weeks of gestation [ 32 ], all results lower than our prevalence detected. Other studies, conducted by Ji, detected similar prevalence of C.trachomatis in women with normal and abnormal cytology, 7.1 and 7.2%, respectively, in China [ 5 ] and Costa Lira, detected to genital C.trachomatis in 9.02% in women who used public health services with abnormal cytology [ 25 ].…”
Section: Discussioncontrasting
confidence: 93%
“…These results are in concordance with a study from India, which detected more prevalence of C.trachomatis in patients with abnormal cytology (31.5%) in comparison with normal cytology (5.8%) [28]. On the other hand, other studies showed different results, such as local studies: Jordá, detected 8.5% C.trachomatis prevalence in symptomatic and asymptomatic women [29] and Kiguen, 6.9% in pregnant women [30], all results lower than our prevalence detected. Other studies, conducted by Ji, detected similar prevalence of C.trachomatis in women with normal and abnormal cytology, 7.1% and 7.2%, respectively [5] and Costa Lira, detected to genital C.trachomatis in 9.02% [24].…”
Section: Discussionsupporting
confidence: 90%
“…Chlamydia trachomatis (CT) causes the most prevalent bacterial sexual transmitted infection (STI) in the world [1]. Based on the 2018 global STI surveillance from World Health Organization (WHO), global estimation of new CT cases in 2016 was 127 million [2].…”
Section: Introductionmentioning
confidence: 99%